IMPLEMENTASI KEBIJAKAN KEPALA PASAR DALAM PROGAM K3 (KEBERSIHAN, KEAMANAN DAN KETERTIBAN) DI PERUSAHAAN DAERAH PASAR PAKUAN JAYA KOTA BOGOR - Louhenapessy, Adi Mandala; Amri, Chairul; Pratidina, Ginung (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2015)
Control of street vendors in Kebun Flower Market is still not optimal, it can be seen still occur kesemerawutan, untidiness and traffic congestion. In the implementation of program policies K3, influenced by factors such success standards and policy objectives, resource policies, communication between the organization and implementation of the activities, characteristics agency / implementing agency policies, attitudes implementing policies,socio-economic conditions and politik.Tujuan research conducted is to know the implementation of K3, K3 and program barriers K3 program at the Companys efforts Pasar Jaya Pakuan Bogor. The research method using descriptive and qualitative approach. The results of market research head of policy implementation in which the implementation of the program K3 K3 picket system, controlling the implementation of a merchant, theimplementation of hygiene supervision, implementation of the billing service charge, and coordination with the village, and babinmas babinsa.Key Words : implementation Policy, Head of Markets, K3 Program